Immature psychological defense mechanisms and the misrepresentations of some sex researchers - Brody, Stuart (2012)
The authors reply to a quartet of recent articles in this journal. We detail certain misrepresentations and the dismissal of existing research in those articles (including attempts at denial of the repeatedly documented association of lack of vaginal orgasm with greater use of immature psychological defense mechanisms and other indices of poorer health). The authors also call for a less defensive and less doctrinaire approach to sex research, especially, but not exclusively, when the prevailing ideology in the fields of sexology might be undermining optimal health.